Recent advances in nanomedicine design strategies for targeting subcellular structures - Defeng Ye; Hua Liu; Enci Dai; Jiang Fan; Liang Wu (iScience)
Summary: The current state of cancer treatment has encountered limitations, with each method having its own drawbacks. The emergence of nanotechnology in recent years has highlighted its potential in overcoming these limitations. Nanomedicine offers various drug delivery mechanisms, including passive, active, and endogenous targeting, with the advantage of modifiability and shapability. This flexibility enables researchers to develop tailored treatments for different types of tumors and populations. As nanodrug technology evolves from first to third generation, the focus is now on achieving precise drug delivery by targeting subcellular structures within tumors. This review summarizes the progress made in subcellular structure-targeted nanodrugs over the past 5 years, highlighting design strategies for targeting mitochondria, lysosomes, endoplasmic reticulum, Golgi apparatus, and cytoskeleton. The review also addresses the current status, limitations, and future directions about the research of nanodrugs.